Penyuntikan Human Wharton’s Jelly Mesenchymal Stem Cells terhadap Perbaikan Fungsi Testis pada Tikus Tua Fisiologis (HUMAN WHARTON’S JELLY MESENCHYMAL STEM CELLS INJECTION AMELIORATE TESTICULAR FUNCTION ON PHYSIOLOGICAL AGING MALE RATS) - Fitrianto, Alif Iman; Utami, Adkhilni; Astini, Wining; Dwijayanti, Adisti; Suyatna, Frans Dhyanagiri; Yaprianto, Kelvin; Bachtiar, Indra; Adnyane, I Ketut Mudite; Boediono, Arief (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
The most common therapy on men who suffered fertility decline due to aging was called “T Therapy”, but that’s therapy has long-term risks of sexual dysfunction, metabolic syndrome, prostate, and cardiovascular system. Stem cells are an alternative therapy can be used for ameliorate testicular fuction because of their ability to differentiate into various cell types. The aim of this study was to evaluate the injection of hWJ-MSC in physiologic aging male rats on testicular function. This study was used 3 young male rats (8-12 weeks) and 6 physiological aging male rats (22-24 months) which divided into 3 groups, (i) the young rats, (ii) physiological aging male rats, and (iii) physiological aging male rats that injected with hWJ-MSCs. The young rat group did not give any treatment, physiological aging male rats received NaCl (0.9%) 0.4 mL, and the treatment group received 1x106 cells/kg BW of hWJ-MSCs. The observations were performed on the macroscopical and histological analysis. The result indicates that the younger group had the lowest body weight (154.6 g) and the percentage of the testis weight on the body weight was highest (2.2%) compared to the other groups (P>0.05). The physiological aging rats group had the smallest tubule (9726.9 ìm2) with a largest interstitial area (1117.1 ìm2) compared the other groups (P>0.05). After injection of hWJ-MSC, the tubule area became wider followed by narrowing of the interstitial area (P>0.05). The difference in the body weights is due to the different age of the rat. Improvement of tubule area and interstitial area due to the ability of hWJ-MSCs to improve spermatogenic cells within the tubule. Injection of hWJ-MSCs has been shown to increase fertility in aging rats.